A STUDY ON SIGNIFICANT INFLUENCE OF E-COMMERCE ADOPTION IN AGRICULTURAL SECTOR THROUGHOUT THE COVID-19: BENEFITS AND LIMITATIONS - Reddy, P. Madhu Kumar; Kumar, A. Rama (Indian Journal of Finance and Banking, 2021)
Agriculture is the solution to the overall development of any country. The internet lasts to become more widespread among people who transact with the agricultural business of any type. The incomplete health crisis about COVID 19 has affected all communities Frontline Health Responders are a priority for countries in saving the lives of the people suffering from this disease. The government has taken action since the Coronavirus hit created an extraordinary situation. India initially announced a three-week nationwide lockdown until the middle of April, after that was extended to achieve satisfactory control of the virus outbreak. In these tough times how Indian farmers react to the crisis and the actions taken by the government to help farmers across the country. The main objective of the study is to analyze the impact of e-commerce on the agricultural sector throughout the Covid 19 pandemic. The study employs samples from farmers of the Warangal and Nalgonda districts. The purpose of the study is to examine the E-commerce sources selected for the agriculture sector and Reasons for using e-commerce in the agriculture and Overall satisfaction on utilization of e-commerce in agriculture sector throughout covid-19. The result reveals that farmers started benefiting from the use of e-commerce in their agriculture. The findings of the study suggest that government should take little more initiation in training and supplying them with agricultural inputs with subsidies. The study briefly explains the Objectives, Hypothesis, Data analysis, Impact, Role, Benefits, and Limitations of E-Commerce in the agricultural sector throughout covid-19. JEL Classification Codes: J43, N5, Q13, L81, P32.